MARK-AGE standard operating procedures (SOPs): A successful effort. (November 2015) - Moreno-Villanueva, María; Capri, Miriam; Breusing, Nicolle; Siepelmeyer, Anne; Sevini, Federica; Ghezzo, Alessandro; Craen, Anton J.M.de; Hervonen, Antti; Hurme, Mikko; Schön, Christiane; Grune, Tilman; Franceschi, Claudio; et al.
Highlights: Standard operating procedures for sample collection and preparation within MARK-AGE. Samples processing following a master protocol elaborated for MARK-AGE purposes. Temporary storage of MARK-AGE samples at a central Biobank. Logistic challenges of MARK-AGE project. Abstract: Within the MARK-AGE project, a population study (3337 subjects) was conducted to identify a set of biomarkers of ageing which, as a combination of parameters with appropriate weighting, would measure biological age better than any single marker. The MARK-AGE project involves 14 European countries and a total of 26 research centres. In such a study, standard operating procedures (SOPs) are an essential task, which are binding for all MARK-AGE Beneficiaries. The SOPs cover all aspects of subject's recruitment, collection, shipment and distribution of biological samples (blood and its components, buccal mucosa cells or BMC and urine) as well as the anthropometric measurements and questionnaires.